PENGARUH TEKANAN SEALING TURBIN TERHADAP KEVAKUMAN KONDENSOR PADA TURBIN UAP UNIT 4 PLTU PT BINTAN ALUMINA INDONESIA - Fajar Masdiantoro; Didi Istardi (JURNAL TELISKA, 2026)
The condenser vacuum of Unit 4 at the PT Bintan Alumina Indonesia (PT BAI) steam power plant exhibits an unusually high sensitivity to turbine gland sealing pressure, resulting in operational challenges that are not observed in comparable generating units. This study investigates the relationship between sealing pressure and condenser vacuum, identifies the optimal sealing-pressure range required to maintain the target condenser vacuum of −94 to −95 kPa, and characterizes the associated operating fluctuations. Operational data comprising 32 weekly observations collected from the Distributed Control System during August–November 2025 at a turbine load of 14–15 MW were analyzed using descriptive statistics, Pearson correlation, and linear regression. The results reveal a strong negative correlation between sealing pressure and condenser vacuum (r = −0.8395), with a coefficient of determination of R² = 0.7048, indicating that approximately 70.5% of the variation in condenser vacuum is explained by changes in sealing pressure. The resulting regression model, ŷ = −0.3853x − 79.8294, predicts an optimal sealing-pressure range of 36.77–39.37 kPa for maintaining the desired condenser vacuum. The observed average operating pressure of 37.16 kPa lies within this optimal range, confirming the suitability of current operating practice. A comparison with the manufacturer's design exhaust pressure (6.1 kPa absolute) further supports the consistency of the identified operating range, although the comparison is based on standard atmospheric pressure because site-specific barometric data were unavailable. These findings demonstrate that effective control of turbine gland sealing pressure is essential for maintaining condenser vacuum and improving the operational efficiency and stability of the steam power plant. Keywords : sealing pressure, condenser vacuum, steam turbine, Pearson correlation, linear regression